2015
DOI: 10.1159/000431021
|View full text |Cite
|
Sign up to set email alerts
|

Shaping the Reproductive System: Role of Semaphorins in Gonadotropin-Releasing Hormone Development and Function

Abstract: The semaphorin proteins, which contribute to the morphogenesis and homeostasis of a wide range of systems, are among the best-studied families of guidance cues. Much recent research has focused on the role of semaphorins in the development and adult activity of hormone systems and, reciprocally, how circulating reproductive hormones regulate their expression and function. Specifically, several reports have focused on the molecular mechanisms underlying the effects of semaphorins on the migration, survival and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 142 publications
1
13
0
2
Order By: Relevance
“…By performing in situ hybridization against Sema3A and Slit1 on control and Arx-1 null mice we confirmed that the forebrain is a large source of repellent molecules, which in concert, might prevent the olfactory and vomeronasal fibers, but not the TN nor the GnRH-1ns, from invading the brain (Renzi et al, 2000;Nguyen-Ba-Charvet et al, 2008). As shown previously, we observed that the Sema3 receptors, NRP1 and NRP2, are expressed by olfactory and vomeronasal neurons projecting to different regions of the MOB and AOB (Cloutier et al, 2002;Walz et al, 2002;Cloutier et al, 2004;Taku et al, 2016); however we could only detect NRP1 but not NRP2 immuno-reactivity on GnRH-1ns and TN axons Hanchate et al, 2012;Giacobini and Prevot, 2013;Giacobini, 2015). By performing in situ hybridization against Sema3A in combination with immunofluorescence for GnRH-1 and Peripherin, we observed that the TN and GnRH-1 invade the brain crossing a source of Sema3A.…”
Section: ) Led Us To Question Whether This Link Was Truly Causalsupporting
confidence: 62%
“…By performing in situ hybridization against Sema3A and Slit1 on control and Arx-1 null mice we confirmed that the forebrain is a large source of repellent molecules, which in concert, might prevent the olfactory and vomeronasal fibers, but not the TN nor the GnRH-1ns, from invading the brain (Renzi et al, 2000;Nguyen-Ba-Charvet et al, 2008). As shown previously, we observed that the Sema3 receptors, NRP1 and NRP2, are expressed by olfactory and vomeronasal neurons projecting to different regions of the MOB and AOB (Cloutier et al, 2002;Walz et al, 2002;Cloutier et al, 2004;Taku et al, 2016); however we could only detect NRP1 but not NRP2 immuno-reactivity on GnRH-1ns and TN axons Hanchate et al, 2012;Giacobini and Prevot, 2013;Giacobini, 2015). By performing in situ hybridization against Sema3A in combination with immunofluorescence for GnRH-1 and Peripherin, we observed that the TN and GnRH-1 invade the brain crossing a source of Sema3A.…”
Section: ) Led Us To Question Whether This Link Was Truly Causalsupporting
confidence: 62%
“…By performing ISH against Sema3A and Slit1 on control and Arx-1 null mice we confirmed that the forebrain is a large source of repellent molecules, which, in concert, might prevent the olfactory and vomeronasal fibers, but not the TN nor the GnRH-1 ns, from invading the brain ( Nguyen-Ba-Charvet et al, 2008 ; Renzi et al, 2000 ). We observed that the Sema3 receptors, NRP1 and NRP2, are expressed by olfactory and vomeronasal neurons projecting to different regions of the MOB and AOB ( Cloutier et al, 2002 , 2004 ; Taku et al, 2016 ; Walz et al, 2002 ); however, we could only detect NRP1 but not NRP2 immuno-reactivity on GnRH-1 ns and TN axons ( Cariboni et al, 2011 ; Giacobini, 2015 ; Giacobini and Prevot, 2013 ; Hanchate et al, 2012 ). By performing ISH against Sema3A in combination with immunofluorescence for GnRH-1 and Peripherin, we observed that the TN and GnRH-1 invade the brain crossing a source of Sema3A.…”
Section: Discussionmentioning
confidence: 61%
“…Accordingly, defects in the organization and/or function of the GnRH system cause heterogeneous reproductive disorders that are characterized by a reduction or failure of sexual competences4344. In Sema7A ko males, a suboptimal number of GnRH neurons leads to impaired testicular growth19, which we found to be associated with lowered levels of circulating TST, reduced androgen receptor expression in the OB, and the absence of a preference/attraction towards opposite-sex smells and/or individuals that is not associated to altered olfactory perception and/or attraction to social cues.…”
Section: Discussionmentioning
confidence: 99%